The extent and distribution of joint conservation-development funding in the tropics - Reed, J.; Oldekop, J.; Barlow, J.; Carmenta, R.; Geldmann, J.; Ickowitz, A.; Narulita, S.; Rahman, S.A.; Vianen, J. van; Yanou, M.; Sunderland, T.C.H. (Elsevier, 2020)
Despite ongoing debates about the viability of sustaining economic growth while maintaining environmental integrity, international sustainability agendas increasingly propose reconciling socio-economic development and global environmental goals. Achieving these goals is impeded by limited funding and a lack of information on where financial flows to integrate environment and development are targeted. We analyze World Bank and Global Environment Facility data to investigate the extent and distribution of such funding across the tropics. We find a misalignment between funding flows and need with highly biodiverse, low development (HBLD) countries receiving no more funding than non-HBLD countries. Countries with low biodiversity receive more funding than highly biodiverse countries and there was no statistical association between a country's development status and funds received. Rather than environment-development need, funding appears to be driven by governance and political-economic factors. Future research should investigate how such factors and funding flows are associated with conservation and development outcomes.